CASE STUDY OF HOST AND ENVIRONMENT FACTORS ON DHF INCIDENCE IN LIMA PULUH DISTRICT: Studi Kasus Faktor Host dan Lingkungan Terhadap Kejadian DBD di Kecamatan Lima Puluh - Tarianna Ginting; Putri Yunita Pane; Eka Lolita Eliyanti Pakpahan; Dameria Gultom; Sari Indriyani (Jurnal Berkala Epidemiologi, 2023)
Background: In the last fifty years, dengue hemorrhagic fever (DHF) has increased 30 times in 100 endemic countries. As a tropical country, Indonesia is one of the endemic countries for DHF cases, which often cause "extraordinary events". Purpose: This research aims to analyze the factors contributing to DHF, including individual and environmental factors. Methods: In November 2022, the unmatched case-control research method was retrospectively used. All DHF cases in Lima Puluh District between January and August 2022, totalling 26 cases, made up the population of this study. The sample in this study was taken based on the total sampling method. The sample consisted of 26 respondents in the case group (those affected by DHF) and 52 respondents in the control group with inclusion criteria (not affected by DHF, distance from house ± 50 meters, age criteria, sex according to the case group) and exclusion criteria (not willing to be a respondent, not in place). The total sample size is 78 respondents, consisting of 26 respondents in the case group and 52 respondents in the control group, with a ratio of 1:2. Results: Based on the results of the chi-square analysis conducted. There was no significant relationship between gender (p = 0.09) and the habit of hanging clothes (p = 0.06) with the occurrence of DHF in Lima Puluh District in 2022. The results of the logistic regression test stated that all host and environmental factors did not have the most dominant variable in the incidence of DHF in Lima Puluh District in 2022. Conclusion: The variable of the existence of breeding places is a dominant factor in the occurrence of DHF in Lima Puluh District in 2022.